Evidence that Crystal Facet Orientation Dictates Oxygen Evolution Intermediates on Rutile Manganese Oxide. (16th February 2018) - Kakizaki, Hirotaka; Ooka, Hideshi; Hayashi, Toru; Yamaguchi, Akira; Bonnet‐Mercier, Nadège; Hashimoto, Kazuhito; Nakamura, Ryuhei
Abstract: Elucidating the mechanism that differentiates the oxygen‐evolving center of photosystem II with its inorganic counterpart is crucial to develop efficient catalysts for the oxygen evolution reaction (OER). Previous studies have suggested that the larger overpotential for MnO2 catalysts under neutral conditions may result from the instability of the Mn 3+ intermediate to charge disproportionation. Here, by monitoring the surface intermediates of electrochemical OER on rutile MnO2 with different facet orientations, a correlation between the stability of the intermediate species and crystal facets is confirmed explicitly for the first time. The coverage of the Mn 3+ intermediate is found to be 11‐fold higher on the metastable (101) surfaces compared to (110) surfaces, leading to the superior OER activity of (101) surfaces. The difference in OER activity may result from the difference in surface electronic states of Mn 3+, where interlayer charge comproportionation of Mn 2+ and Mn 4+ to generate two Mn 3+ species is favored on (101) facets. Considering the fact that the OER enzyme accommodates Mn 3+ stably during the Kok cycle, the enhanced OER activity of the rutile MnO2 catalyst with a metastable surface highlights the importance of mimicking not only the crystal structure but also the electronic structure of the targeted natural enzyme. Abstract : The oxygen evolution activity of MnO2 with different facet orientations is studied to gain insight into the role of Mn 3+ and allow for the rational design of functional analogs of the biological oxygen evolution center. (101) surfaces display higher activity compared to (110) surfaces despite having the same bulk crystal structure, due to the increased stabilization of Mn 3+ on (101).